Enhanced circularly polarized luminescence of chiral Eu(iii) coordination polymers with structural strain. Issue 3 (3rd January 2023) - Tsurui, Makoto; Kitagawa, Yuichi; Shoji, Sunao; Fushimi, Koji; Hasegawa, Yasuchika
Abstract : Three types of Eu(iii ) coordination polymers with distorted chiral ligands were prepared for elucidating the relationship between their structural distortions, ligand-to-metal charge transfer, and circularly polarized luminescence properties. Abstract : Three types of Eu(iii ) coordination polymers with different distorted chiral ligands, [Eu(+tfc)3 ( p -dpeb)] n, [Eu(+pfc)3 ( p -dpeb)] n, and [Eu(+hfc)3 ( p -dpeb)] n (+tfc: (+)-3-(trifluoroacetyl)camphorate, +pfc: (+)-3-(pentafluoropropionyl)camphorate, +hfc: (+)-3-(heptafluorobutyryl)camphorate, p -dpeb: 1, 4-bis(diphenylphosphorylethynyl)benzene), were prepared for elucidating the relationship between their structural distortions, ligand-to-metal charge transfer (LMCT), and circularly polarized luminescence (CPL) properties. Their strain factors in the ligands were evaluated using crystallographic data obtained by single-crystal X-ray structural analyses. The characteristics of the LMCT excited states were estimated from theoretical calculations. The introduction of a bulky substituent into the chiral ligand afforded a distorted structure of β-diketonates and changed the direction of the transition electric dipole moments, which are related to the magnitude of the CPL intensity. The CPL dissymmetry factor ( g CPL ) of [Eu(+hfc)3 ( p -dpeb)] n, with a large distorted structure, was −0.22, while those of [Eu(+tfc)3 ( p -dpeb)] n and [Eu(+pfc)3 ( p -dpeb)] n, with small distorted structures, were −0.05 and −0.10, respectively. The controlled steric hindrance of the chiral ligands in Eu(iii ) coordination polymers is one of the strain factors enhancing their CPL properties.